Variation in Practice of the Diagnostic Workup of Asymptomatic Patients Diagnosed with Invasive Breast Cancer - Chagpar, Anees B.; Babiera, Gildy V.; Aguirre, Jose; Hunt, Kelly K.; Hughes, Tyler (Frontiers in Oncology, 2016)
Introduction: Breast cancer is frequently diagnosed, yet variation remains in terms of practice patterns in presurgical workup. We sought to determine factors associated with this variation. Methods: An anonymous web-based survey was distributed to surgeons regarding their practices. Statistical analyses were conducted using SPSS. Results: 253 surgeons responded to the survey. 17.0% were in academic practice, 37.5%% were hospital employed, and 41.5% were in private practice. 53.3% claimed that > 50% of their practice was breast-related. Surgeons were asked how often they would use various tests in the workup of an otherwise healthy asymptomatic patients, presenting with a non-palpable mammographic abnormality and a core needle biopsy showing invasive breast cancer. 23.5% stated they always would obtain a breast ultrasound, 17.2% stated they never would. 12.8% stated they never order a breast MRI; 4.1% always would. Workup of patients did not vary significantly based on number of years in practice nor practice setting. However, those whose practice was >50% breast were more likely to state that they would always order a breast ultrasound (32.5% vs. 12.9%, p<0.001), and less likely to state they would never order a breast MRI (3.4% vs. 25.8%, p<0.001). However, the proportions of surgeons who would always order a breast MRI was similar in the two groups (3.4% and 3.2%, respectively). Conclusions: These data highlight the lack of uniformity in the workup of asymptomatic patients presenting with non-palpable breast cancers, pointing to potential areas for improving value by minimizing variability.